HUBUNGAN HIPERTENSI DENGAN KEJADIAN STROKE PADA LANSIA DI WILAYAH KERJAPUSKESMAS SEKUPANG KELURAHAN TANJUNG RIAU KOTA BATAM - Ditte Ayu Suntara; Nelli Roza; Aprillia Rahmah (Sekolah Tinggi Pariwisata Mataram, 2021)
Stroke Prevalence Globally, based on the Stroke Forum (2015), 15 million people have a stroke each year, one third die and the rest have permanent disabilities. In Indonesia, stroke ranks third after asthma and cancer. The results of Riskesdas 2018, the percentage of stroke presentations was 4.4%. Batam City has elderly with 2,085 cases and the most in Sekupang Health Center with 242 cases. One of the risk factors for stroke is hypertension. This study aims to determine the relationship between hypertension and the incidence of stroke in the elderly with a case control design. The number of respondents in this study were 23 elderly in each group with consecutive sampling. The results of the study were obtained from 23 elderly in the case group, it was found that 21 elderly with hypertension (45.7%) and only 2 elderly (8.7%) without hypertension had a stroke, while 23 elderly in the control group found 8 elderly people with hypertension. had hypertension (34.8%) and 15 elderly who did not have hypertension (65.2%). The results of the chi square statistical test showed the relationship between hypertension and the incidence of stroke (p value = 0.000 with α 0.05) and OR = 19.68.